Green crime, territorial resistance and the metabolic rift in Brazil’s Amazon and Cerrado biomes - Garvey, Brian (Criminological encounters, 2022)
This paper draws on three case studies in the Amazon and Cerrado biomes of Brazil, where the encroachment of hydroenergy, mining and agroindustrial complexes into rural, forest and riverine communities has triggered environmental destruction and escalating human rights abuses. By unveiling the links between localised, violent land grabs and the broader corporate strategies of resource capture and land speculation, the paper contrasts the destructive, and often criminal territorial advance of these activities with the corporeal and cultural reproduction of communities whose resistance is an obstacle to further accumulation and environmental harm. The contrast and conflict between these distinct organisational and productive forms, imbued with massive power asymmetries, invites a broader conception of labour-capital tensions and highlight contradictions within state making apparatus with implications for both human rights and environmental harm. The paper thus builds upon theoretical advances in understanding human-nature metabolic relations to depict how corporeal rupture is intimately tied to environmental exploitation in these biodiverse territories. It insists that attention to the motivations and outcomes of rights violations at a range of scales is required to understand the perpetuation of these transgressions, while closer attention to the episteme and strategies of the communities may offer pathways to a social and ecologically committed future.